Association Between Different DVT Prevention Methods and Outcomes of Septic Shock Caused by Intestinal Perforation in China: A Cross-Sectional Study - Wang, Lu; Ma, Xudong; He, Huaiwu; Su, Longxiang; Guo, Yanhong; Shan, Guangliang; Wang, Ye; Zhou, Xiang; Liu, Dawei; Long, Yun (Frontiers in Medicine, 2022)
Introduction: Septic shock, largely caused by intestinal perforation, is the most common critical illness in intensive care unit (ICU). As an important quality control strategy in ICU, deep vein thrombosis (DVT) prevention is routinely used in the treatment of septic shock. Nevertheless, the effects of DVT prevention on septic shock are not fully revealed. This study was thus designed to investigate the effects of DVT prevention on septic shock caused by intestinal perforation in China. Methods: A total of 463 hospitals were enrolled in a survey, led by the China National Critical Care Quality Control Center (China NCCQC) from January 1, 2018 to December 31, 2018. The association between DVT prevention, including pharmacological prophylaxis and mechanical prophylaxis, and outcomes, such as prognosis, complications, hospital stays, and hospitalization costs, was determined in the present study. Main results: Notably, the increased rates of DVT prevention were not associated with the onset of complications in patients with septic shock caused by intestinal perforation (p > 0.05). In addition, even though increased DVT prevention did not affect hospital stays, it significantly decreased the discharge rates without doctor's order in patients with septic shock caused by intestinal perforation (p < 0.05). Nevertheless, it should be noted that the rates of pharmacological prophylaxis but not mechanical prophylaxis were significantly associated with the costs of septic shock caused by intestinal perforation (p < 0.05). Although increased total rates of DVT prevention and the rates of mechanical prophylaxis did not reduce the mortality in patients with septic shock caused by intestinal perforation, the higher frequent intervention using pharmacological prophylaxis indicated the lower mortality of these patients (p < 0.05). Conclusions: DVT prevention by any means is a safe therapeutic strategy for treating septic shock caused by intestinal perforation, and pharmacological prophylaxis reduced the mortality of patients with septic shock caused by intestinal perforation.